Implementation of Integrated Quality Management in Improving the Quality of MTs Graduates in Pondok Pesantren Kholafiyah - Acep Acep; Iim Wasliman; Hendi Suhendraya Muchtar (International Journal of Nusantara Islam, 2021)
The background of this research MTs inferior quality of graduates, allegedly because not terimplementasinya m anagement m utu t erpadu (MMT) so that the performance of education and learning is still weak. The research objective to describe the preparation, steps, processes, supervision, results, problems, solutions and innovative ideas in the implementation of m anagement m utu t erpadu in improving the quality of graduates MTs in Kholafiyah Pontren environment. The research foundation used is theological, philosophical, theoretical, and tual concepts , the six value systems, and relevant prior research. Using Edward Sallis' theory of integrated quality management (TQM) with a qualitative approach with descriptive methods . T eknik collecting data through interviews, observation , and documentation study. The research location is MTs Assalam Darul Faizah Warungkiara and MTs Al-Ma'tuq Cisaat Sukabumi Regency . The results of the research are as follows: (1) preparation for the implementation of MMT has been going well, starting with the preparation of programs and work plans for Islamic boarding schools in macro and micro MTs, (2) MMT steps begin with the formulation of the vision, mission, and objectives of the pesantren. holistically and integrated with the vision, mission and objectives of MTs, (3) the implementation process of MMT in general is related to quality learning services, (4) supervision in MMT implementation is carried out through four techniques, namely coaching, monitoring, guidance, and performance appraisal, (5) the results of the implementation of MMT produced a generation that is faithful, devoted, berakhlakul karimah, academic achievement and non-academic, (6) the problem that ditemu right in the implementation of MMT is partly HR and education Personnel not in accordance with educational qualifications and operational costs of education not yet balanced with the amount of madrasah income, (7) efforts made to overcome the problem d ith a regeneration program for teachers and education personnel through lectures in accordance with the needs of the institution. For educational operational costs, there is a movement to finance a cross-subsidized system from parents / guardians of students with advanced economic conditions (aghniya), and (8) innovative ideas in implementing MMT to improve the quality of MTs graduates in the Pontren Kholafiyah environment, namely the application of the “integrated quality management model. Islamic boarding schools integrated into madrasah education units. The implication of the research results is that the implementation of MMT can improve the quality of graduates, so every education unit must apply it . Recommendations to boarding school leaders who manage formal education units always give more authority to manage madrasah-based management.